2017
DOI: 10.1002/app.45327
|View full text |Cite
|
Sign up to set email alerts
|

The effects of graphene oxide on the properties and drug delivery of konjac glucomannan hydrogel

Abstract: Konjac glucomannan (KGM) hydrogel has good potential application in food and medical science, although to achieve this, the physical and mechanical properties need further improvement. In this study, graphene oxide (GO) was used to improve the functionality of KGM hydrogel. KGM/GO hydrogels were prepared by freezing the alkaline KGM/GO sols. Rotational rheometer was used to study the rheological properties of different alkaline KGM/GO sols. Fourier transform infrared, Raman, differential scanning calorimetry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Due to the weak properties, pure Da-KGM hydrogel prepared by freeze-thawing method cannot meet actual applications, therefore, some additives are used in the procedure. graphene oxide (GO) is a common additive for enhancing properties of materials, Yuan et al [ 32 ] successfully prepared KGM/GO hydrogels by alkaline processing followed freeze-thawing, KGM/GO hydrogel showed a compact structure and decreased pore size comparing with pure KGM hydrogel. The porous structures of KGM/GO hydrogel had great specific surface area, and provided a possibility for drug storage and sustained delivery.…”
Section: Preparation Of Konjac Glucomannan (Kgm) Gel and Its Micromentioning
confidence: 99%
“…Due to the weak properties, pure Da-KGM hydrogel prepared by freeze-thawing method cannot meet actual applications, therefore, some additives are used in the procedure. graphene oxide (GO) is a common additive for enhancing properties of materials, Yuan et al [ 32 ] successfully prepared KGM/GO hydrogels by alkaline processing followed freeze-thawing, KGM/GO hydrogel showed a compact structure and decreased pore size comparing with pure KGM hydrogel. The porous structures of KGM/GO hydrogel had great specific surface area, and provided a possibility for drug storage and sustained delivery.…”
Section: Preparation Of Konjac Glucomannan (Kgm) Gel and Its Micromentioning
confidence: 99%
“…Next, to characterize the interaction between GO and MeHA hydrogel network, we performed Fourier Transform Infrared (FTIR) spectroscopy on hydrogel and hydrogel‐GO films (Figure 1F). GO contains carboxyl groups which can form hydrogen bonds with the amine and/or hydroxyl groups present in the MeHA hydrogel [36–38] . The N−H stretching vibration peak at 3300 in the hydrogel‐only spectrum has been shifted to 3305 in the hydrogel‐GO spectrum, indicating the formation of hydrogen bonds [36] .…”
Section: Resultsmentioning
confidence: 99%
“…GO contains carboxyl groups which can form hydrogen bonds with the amine and/or hydroxyl groups present in the MeHA hydrogel. [36][37][38] The NÀ H stretching vibration peak at 3300 in the hydrogel-only spectrum has been shifted to 3305 in the hydrogel-GO spectrum, indicating the formation of hydrogen bonds. [36] The NÀ H bending peak at 1610 has been also shifted to 1600 in the hydrogel-GO spectrum, further suggesting hydrogen bond formation between GO and the MeHA hydrogel.…”
Section: Hmn-gona Fabrication and Characterizationmentioning
confidence: 99%
“…The sharpest band of the KPPA4 spectrum is 1622.1 cm −1 , which corresponds to the carbonyl stretching vibration. However, for the KPPA0, KPPA1, KPPA2, KPPA3 and KPPA4 cryogels, the stretching vibrations of –OH groups were generated at 3442.8, 3439.5, 3435.7, 3429.3 and 3425.6 cm −1 , respectively; while the bending vibrations of –C–H groups occurred at 1645.2, 1631.3, 1627.5,1627.2 and 1622.1 cm −1 [ 50 ], respectively. The shift of these absorption peaks indicated that the intermolecular hydrogen bonding between PDA and KGM/PLA molecular chains was formed in the cryogels.…”
Section: Resultsmentioning
confidence: 99%